Status and Distribution of Mangroves in India: A Review (International Journal of Food and Nutritional Sciences, 2022)
Spatial distribution patterns along the Indian coastline, focusing on key regions such as theSundarbans, Andaman and Nicobar Islands, Gulf of Kutch, Maharashtra, Gujrat and Odisha.Environmental factors, including salinity, tidal range, and sediment type, are discussed as criticalinfluencers of mangrove composition and structure. Satellite imagery analysis, exemplified by Giri etal. (2011), reveals the impact of anthropogenic activities, such as coastal development andaquaculture, on mangrove cover over time. Conservation implications are highlighted, emphasizingthe need for tailored initiatives that address specific threats faced by diverse mangrove ecosystems inIndia.